Exploring the application of drone technology for construction sites management in Malaysia - Chooi, Yen Sing (2024)
The construction industry is an essential sector that provides economic and social stability to the country. As construction projects continue to grow in complexity and size, the adaptation of modern technology is necessary to achieve the current standards of construction projects. In particular, this research will focus on drone technology as one of the technologies of the fourth industrial revolution to be utilised for construction site management. Therefore, the aim of this study is to explore the applications of drone technology for construction site management in Malaysia. Literature review was conducted to identify all the applications, benefits and barriers of utilising drone technology for construction site management in Malaysia. The research was conducted in the Klang Valley area, where the data collected from the respondents that are made of contractors and consultants who participated in the questionnaire survey. The survey is carried out through convenience sampling followed by snowball sampling. The research was carried out to determine the agreement level of the respondents on the applications, benefits and barriers of drone technology and also to determine if there are any significant differences between the two group. The questionnaire survey uses a 5-Point Likert Scale system for the respondents to rate their agreement level on the applications, benefits and barriers of drone technology in construction site management. The data collected from the respondents was tested to have a good internal consistency and reliability through the Cronbach Alpha reliability Test. From the data, it was identified that the most common application of drone technology is for inspection tasks, as the benefits that seen the highest agreement level is the reduction of safety risks. However, length data processing period has the highest agreement level on being the barrier of using drone technology. This research can be an essential asset for construction stakeholders who wish to improve productivity and quality of their projects and also act as a starting point for future research.